State of the art of home economics extension program under the devolution and its implication to countryside development - Rodriguez, Ophelia B. (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2000)
The study aimed at determining the status of the Home Economics Extension program (HEEP) under the devolution and its implication to countryside development. It established the HEEP historical development over that past seven decades and sought the opinion of the respondents on the program's relevance. The investigation utilized documentary evidence, survey questionnaire, interview, and focus group discussion in the collection of data. Three groups comprised the subjects of the study, namely: the HEEP implementors (Home Management Technicians), program participants (Rural Improvement Club Presidents), the management (Municipal Agricultural Officers, Vice-Mayors,and Chairmen of Agriculture). Results revealed that the HEEP (renamed as Farm Home Resources Management Program- FHRMP) operationalization under devolution was a carry over of its former program design. However, implementation of its component project/ activities diminished due to lack of funds, manpower, and low priority accorded to the program by the Local chief executives.